Optimal scheduling of a virtual power plant with demand response in short-term electricity market - Rashidizadeh-Kermani, Homa; Vahedipour-Dahraie, Mostafa; Shafie-khah, Miadreza; Osório, Gerardo J.; Catalão, João P. S. (IEEE, 2020)
This paper presents an optimal bidding and offering strategy for a virtual power plant (VPP), which participates in day-ahead (DA) and balancing markets. The VPP comprises distributed energy resources, plug-in electric vehicles (PEVs) and flexible demands. The objective of the problem is maximizing the VPP’s profit while demand response (DR) providers who aggregated the loads try to supply the required demand under their jurisdiction with minimum costs. The proposed optimization problem is formulated as a bi-level stochastic scheduling programming to address uncertainties in DA and balancing electricity prices, renewable energy source’s (RES) and DR relationship. Simulation results demonstrate the applicability and effectiveness of the proposed model to any real markets. Also, numerical results show that the flexibility of responsive loads and PEVs can improve the VPP operator's energy management and increase its expected profit.
Keywords: demand response; electricity market; mixed-integer linear programming; virtual power plants; stochastic scheduling; fi=Sähkötekniikka|en=Electrical Engineering|